Model Pendidikan Pembuatan Keris Dari Masa Ke Masa Di Sumenep Madura - Khairul Umam (STAI Al-Mas'udiyah, 2024)
Keris is one of the world's recognized intangible cultural heritages. This is clearly stated in Unesco's Representative List of Humanity in 2008. From data found by Unggul, the largest number of keris craftsmen in Southeast Asia are in Sumenep. In fact, from the data he obtained, from 2012 to 2014, the number of keris craftsmen increased until it reached around 600 craftsmen. This is certainly something that is both encouraging and a challenge to continue to maintain. Referring to the data above, of course, the regeneration of keris craftsmen in Sumenep continues to be carried out massively amidst the onslaught of pragmatism, materialism, and pop culture which continues to pressure the younger generation, especially in Indonesia. This requires certain strategies and methods in the regeneration process with learning methods that are able to attract the younger generation. This research intends to explore the learning models carried out by masters from time to time so that they can survive and the number of craftsmen tends to increase to this day. The method used is ethnography with a qualitative approach.